KETUA KPK DALAM BINGKAI MEDIA PADA KASUS KORUPSI GUBERNUR PAPUA DI MEDIA CNNINDONESIA.COM DAN DETIK.COM - Hildansyah, Irdan; Nur, Muhammad Jamiludin; Pauji, Resa Restu (Jurnal Common, 2022)
This study aims to look at the framing carried out by the online media CNN Indonesia.com and Detik.com on the corruption case of the Governor of Papua, Lukas Enembe. This study uses a qualitative research. Thus, this study looks at the meaning of individual or group problems in human life. This study uses Robert Entman's analysis model to identify the framing of CNN Indonesia.com and Detik.com. Data collection was carried out by observing through online media. Researchers saw news about Lukas Enembe in the November period. The researcher then selected news that was relevant to the development of the Lukas Enembe corruption case. The results of this study indicate that CNN Indonesia.com framed the chairman of the KPK, Firli Bahuri, for violating law enforcement ethical standards. Firli Bahuri is also framed as a figure who gave privileges for the corruption suspect meanwhile he has never done it before. Meanwhile, Detik.com's framing of Firli Bahuri has violated the ethical standards of law enforcement. The portion of the news about Lukas Enembe and how his status and health condition is less than the circumstance of the meeting with Firli Bahuri. Detik.com also did not show the information provided by the KPK regarding Firli Bahuri's involvement in the meeting. Entman's model analysis is not sufficient to explain media reality comprehensively. Not all news offers moral choices and problem solved. Due to these limitations, this study requires other analytical tools to explain this phenomenon. A more in-depth investigation with other analytical tools is needed to get a more complete picture in terms of framing. Keywords: Framing, Firli Bahuri, KPK, Lukas Enembe.